The base of party political support in Ireland: A new approach - David Madden (University College Dublin, UCD School of Economics, 2016)
Party politics in Ireland has been characterised as politics without a social base. This paper calculates political concentration indices for party support in Ireland showing how support for a particular party is concentrated according to identifiable dimensions such as income, education and age. Using data from the European Social Survey, these indices are calculated with respect to elections in 2002, 2007 and 2011. There is evidence of a clear social base emerging after the 2011 election with support for the Fine Gael party concentrated amongst the richer and more educated, while support for Sinn Fein is concentrated amongst lower income and less educated. Preliminary data from the 2016 election is consistent with these developments.
Keywords: D72; 330; Party support; social base; concentration index